Brecht, Turkish theater, and Turkish-German literature : reception, adaptation, and innovation after 1960 - Gezen, Ela E., 1977- (Rochester, New York : Camden House, 2018)
Uncovers the central role of Brecht reception in Turkish theater and Turkish-German literature, examining interactions between Turkish and German writers, texts, and contexts.
Frontcover; Contents; List of Illustrations; Acknowledgments; Introduction; 1: Intersections of Politics and Aesthetics: Bertolt Brecht in the Turkish Context; 2: Didactic Realism: Aras Ã#x96;ren and Working-Class Culture; 3: Staged Pasts: Emine Sevgi Ã#x96;zdamarâ#x80;#x99;s Dramatic Aesthetic; Conclusion; Notes; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Brecht, Bertolt, -- 1898-1956 -- Stage history -- Turkey; Brecht, Bertolt, -- 1898-1956 -- Influence; Brecht, Bertolt, -- 1898-1956; German drama -- 20th century -- History and criticism; German literature -- Turkish authors -- History and criticism; Theater -- Turkey -- History -- 20th century; Théâtre allemand -- 20e siècle -- Histoire et critique; Littérature allemande -- Auteurs turcs -- Histoire et critique; DRAMA -- Continental European; LITERARY CRITICISM -- European -- German; German drama; German literature -- Turkish authors; Influence (Literary, artistic, etc.); Theater; Turkey; 1900-1999; 1960s.; Brecht; East and West Germany; German writers; Turkish theater; Turkish writers; Turkish-German literature; adaptation; aesthetics; cultural affairs; cultural integration; culture; innovation; intellectual interchanges; intellectuals; literature emergence; politics; reception; theater practice; Criticism, interpretation, etc; History